Effects of climate change on wet and dry spells in Kelantan River basin using physically-based hydrological model and CMIP6 scenarios - Nurul Afiqah Mohamad Arbai; Masayasu Irie (Journal of Hydrology: Regional Studies)
Study region: Kelantan River basin. Study focus: This study integrated CMIP6 datasets with the Rainfall-Runoff-Inundation (RRI) model to assess the influence of the four main Shared Socio-economic Pathways (SSPs) on the temporal discharge of the Kelantan River. This also encompassed an evaluation of its impact on the changes in design discharge for both high-flow and low-flow conditions. New hydrological insights for the region: The analysis of basin behavior under various SSPs is relatively new in Malaysia; thus, this study was conducted to evaluate the impact on the Kelantan River basin, encompassing wet and dry conditions. Based on the projected precipitation and evapotranspiration, the discharge at the Kelantan River mouth were generated using the RRI model. The climate scenarios of SSP5–8.5 and SSP3–7.0 resulted in the wettest and driest conditions in terms of annual and monthly effective precipitation and discharge patterns. It was predicted that the basin would experience the wettest and driest from 2051 to 2075. The northeast monsoon season was expected to result in a wetter condition, while the southeast monsoon was expected to result in a drier condition. Despite the alterations in the climate, the study found no instance of low precipitation and high evapotranspiration occurring simultaneously. SSP5–8.5 yielded the most extreme design discharge for both wet and dry spells considering the temporal daily variability of the climate scenarios.